Genius habit : how one habit can radically change your work and your life - Garnett, Laura (Recorded Books, Inc., 2019)
Make your job the right jobMaybe you're a young professional just starting to think seriously about what you want out of your career. Maybe you've been job hopping for a few years and haven't found the perfect fit. Or maybe you want to launch your career to a new level and bring fresh energy to your work. In The Genius Habit, performance strategist Laura Garnett shows you how the path to finding long-lasting professional happiness starts with building the habit that makes extraordinary accomplishment all but guaranteed, as well as:The difference between passion and purpose and why one matters more than the otherHow to stop equating achievements with happinessWhy having a mentor is not a necessity for career successThe benefits of continually fine-tuning your career so you are challenged and fulfilled every dayCombining the most recent and exciting research on productivity and performance with Laura's experience guiding dozens of high-level clients to the heights of success, The Genius Habit is a must-read for anyone who believes that work can and should be one of the most rewarding aspects of life.